Survival Prediction After Neurosurgical Resection of Brain Metastases: A Machine Learning Approach. Issue 3 (26th September 2022) - Hulsbergen, Alexander F. C.; Lo, Yu Tung; Awakimjan, Ilia; Kavouridis, Vasileios K.; Phillips, John G.; Smith, Timothy R.; Verhoeff, Joost J. C.; Yu, Kun-Hsing; Broekman, Marike L. D.; Arnaout, Omar
Abstract : BACKGROUND: Current prognostic models for brain metastases (BMs) have been constructed and validated almost entirely with data from patients receiving up-front radiotherapy, leaving uncertainty about surgical patients. OBJECTIVE: To build and validate a model predicting 6-month survival after BM resection using different machine learning algorithms. METHODS: An institutional database of 1062 patients who underwent resection for BM was split into an 80:20 training and testing set. Seven different machine learning algorithms were trained and assessed for performance; an established prognostic model for patients with BM undergoing radiotherapy, the diagnosis-specific graded prognostic assessment, was also evaluated. Model performance was assessed using area under the curve (AUC) and calibration. RESULTS: The logistic regression showed the best performance with an AUC of 0.71 in the hold-out test set, a calibration slope of 0.76, and a calibration intercept of 0.03. The diagnosis-specific graded prognostic assessment had an AUC of 0.66. Patients were stratified into regular-risk, high-risk and very high-risk groups for death at 6 months; these strata strongly predicted both 6-month and longitudinal overall survival ( P < .0005). The model was implemented into a web application that can be accessed through http://brainmets.morethanml.com . CONCLUSION: We developed and internally validated a prediction model that accurately predicts 6-month survival after neurosurgical resection for BM and allows for meaningful risk stratification. Future efforts should focus on external validation of our model.